The Motivic Development in Western Music of Dhamma Likay of King Ajatashatru - ศิริรัตนพันธ, บุญรัตน์ (Rangsit Music Journal, 2018)
The Historical Dhamma Likay of King Ajatashatru, as the production team conceived, directed by Jariya Samanabarami or the Thai-Bollywood star, Ann Mitchai, which I had duties as the music director, arranger and composer was performed in June 2017 at Thailand Cultural Center is a crossed-over music drama. It mixes western musical play structure with Likay (a traditional Thai melodramatic singing play) music and singing style. It also uses various 20th century musical techniques included electronic music and Indian music together. This article will present the main motif of western parts of this work, the meaning and ways I used to create motives which sometime related to the 12-tones system of Arnold Schönberg and bi-tonality. Then the usage of those techniques in the various points of the play are presented. Next, the motivic-development according to function, story and situation of the play are analyzed with meanings. Finally, I will summarize all the ideas again.